Comunicación Política - HU31 - 202101 - Dominguez Navarrete, Cristhiam Roberto (2021)
Description: Communication and politics. Two words, or two social phenomena naturally linked to modern societies. Every day, in front of us, the people we define as politicians use the diverse channels of communication, social media, or those alternative mediums, to broadcasts their messages. At the same time, the media becomes involved, either openly or subtly, politics, taking positions, interpretations, or even, silencing in a very evident way. The course seeks to explore the above mentioned with a dynamic approach, specifying where it originates, how it maintains and how it develops. Our objective will be to learn to observe and understand how different forms of communications are used to transmit ideologies, information, promises, appearances, rumors, and everything related to the political life. Because of this, our attention will be especially focused on images and discourses. Likewise, students will study different strategies of political marketing and analyze their impact on the media. We will work with the understanding that the work of politics is not uniquely exclusive to politicians, but it also involved citizens, civil society, as well as national and international institutions. Purpose: This course, intended for the bachelor degrees in Communication & Journalism and Communication & Corporate Image, has a theoretical approach for students in their VIII and IX cycle. It seeks to develop the general competencies of Citizenship, Critical thinking, and that of Analysis and interpretation of reality.